2018
DOI: 10.1080/14767058.2018.1434141
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in pregnancy: a literature review

Abstract: The risk of using thrombolytics in pregnancy seems reasonable taking into account the risk of death in a life-threatening event, with the majority of cases presented in this article resulting in encouraging outcomes. The complication rate of thrombolytic treatment does not seem higher in pregnant women than in the nonpregnant. Poor fetal outcome occurred in mothers with poor prognosis. Specific consensus recommendations are needed in the use of thrombolytics in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 93 publications
0
37
0
Order By: Relevance
“…Studies have shown that the use of thrombolysis in pregnancy is safe, without any significant increase in maternal deaths or major bleeding events 9–11. However, haemorrhage during parturition or caesarean delivery is a particular risk with fibrinolytic therapy if the patient goes into labour or operative delivery is required, so the benefits of such treatment must be carefully weighed against the risks, particularly in cases of severe pre-eclampsia, when delivery must be expedited.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the use of thrombolysis in pregnancy is safe, without any significant increase in maternal deaths or major bleeding events 9–11. However, haemorrhage during parturition or caesarean delivery is a particular risk with fibrinolytic therapy if the patient goes into labour or operative delivery is required, so the benefits of such treatment must be carefully weighed against the risks, particularly in cases of severe pre-eclampsia, when delivery must be expedited.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of a balance between coagulation and fibrinolysis is of great importance for the perinatal safety of both mothers and infants [16] . A physiologic hypercoagulable state has been demonstrated during pregnancy and the peripartum period [16,17] , which helps to protect women from excessive bleeding during childbirth. Nevertheless, in developed nations, the leading cause of maternal death is thromboembolic disease [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the limited suggestions provided by the PE guidelines have primarily been made based on pooled and analyzed data obtained from case reports; therefore, clinicians should exercise caution when drawing conclusions in actual clinical situations. Gomes et al [ 8 ] studied 65 articles describing the use of thrombolytic agents during pregnancy and maternity and reported that the complication rate of thrombolytic agent use in pregnant women appeared to be the same as that in nonpregnant women. Twenty-five women suffering with PE during the gestational period were included in this review.…”
Section: Discussionmentioning
confidence: 99%